INTENSITAS PENGGUNAAN TIKTOK TERHADAP SISWA KELAS V UPT SDN 73 BONTORITA I DAN UPT SD NEGERI 117 INPRES BONTOMANGAPE - Mutiara Rengganis; Kaharuddin; Idawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the intensity of TikTok usage among fifth-grade students at UPT SDN 73 Bontorita I and UPT SD Negeri 117 Inpres Bontomangape. The research employed a qualitative descriptive approach with data collection techniques including observation, interviews, questionnaires, and documentation. The subjects of the study consisted of students, teachers, and parents.The results show that the intensity of TikTok usage among students is relatively high. Most students access TikTok daily, often more than once a day. The application is frequently used during leisure time, after school, and for durations exceeding 30 minutes per session. Some students also tend to use TikTok at night and before going to school. The activities carried out include watching videos, liking or commenting on content, and creating and uploading videos. For many students, TikTok has become a primary source of entertainment in their daily routines.These findings indicate that TikTok has become an integral part of students’ daily activities with a relatively high level of usage intensity.